2023
DOI: 10.1037/tra0001358
|View full text |Cite
|
Sign up to set email alerts
|

Open science and data sharing in trauma research: Developing a trauma-informed protocol for archiving sensitive qualitative data.

Abstract: Objective: The open science movement seeks to make research more transparent, and to that end, researchers are increasingly expected or required to archive their data in national repositories. In qualitative trauma research, data sharing could compromise participants’ safety, privacy, and confidentiality because narrative data can be more difficult to de-identify fully. There is little guidance in the traumatology literature regarding how to discuss data-sharing requirements with participants during the inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…We believe that including considerations about which materials to eventually make public is a significant benefit of this checklist. By considering ethical issues such as data sharing early, researchers can plan accordingly and include participants' perspectives into the relevant decisions [21,23,56] and thus addressing ethical concerns to sharing qualitative data. We also hold, however, that this tool remains useful even if used exclusively as an internal checklist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that including considerations about which materials to eventually make public is a significant benefit of this checklist. By considering ethical issues such as data sharing early, researchers can plan accordingly and include participants' perspectives into the relevant decisions [21,23,56] and thus addressing ethical concerns to sharing qualitative data. We also hold, however, that this tool remains useful even if used exclusively as an internal checklist.…”
Section: Discussionmentioning
confidence: 99%
“…Transparent research is an ideal, and transparency is best understood on a continuum: research can be more or less transparent and, all things being equal, we should strive to move our practices towards the transparent end of that continuum. By providing practical guidance for more open, transparent qualitative research, we add to a growing literature on openness in qualitative research, including on such topics as pre-registration [19], authorship [20], consent for sharing data [21][22][23], and de-identifying and sharing sensitive qualitative data [24,25].…”
Section: Defining and Understanding Key Terms: Reproducibility Vs Tra...mentioning
confidence: 99%
“…Survivors’ contact information could not be provided to the research team, per the agency's confidentiality policy and the policies of their funders, so the advocates agreed to reach out to survivors to explain the study and request their participation (see Campbell et al, in press for protocol). The advocates noted that it would be challenging to reconnect with these survivors, as many had been hard to find during their court cases (e.g., changes in phone numbers and addresses), and some may not want to discuss the matter further.…”
Section: Methodsmentioning
confidence: 99%
“…To establish confirmability (i.e., the findings reflect the participants’ views, not the researchers’ biases), the PI kept field notes and wrote reflexive memos throughout the project. We kept an audit trail (see above) and conducted triangulation assessments (see above) to ensure that the findings did not reflect the biases of the research team (see Campbell et al, in press for the team's positionality statement and how we engaged our positionalities throughout the conduct of this research).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, data sharing raises ethical questions about participants’ agency and control of their information. Formative studies that have explored how research participants feel about data sharing have found they are generally agreeable because they want to maximize what can be learned from their experiences to help others (Campbell, Goodman-Williams, Engleton, et al, 2023; Kuula, 2011; Mozersky, Parsons, et al, 2020; VandeVusse et al, 2022; Yardley et al, 2014). However, participants emphasized that researchers must seek informed consent for data sharing; consent to participate in the study does not give researchers implicit permission to share the data collected in that study (for consent-language options, see Kaiser, 2009).…”
Section: Ethical Issues To Address When Sharing Qualitative Datamentioning
confidence: 99%